Two new species of free-living marine nematodes of the family Oxystominidae Chitwood, 1935 (Enoplida) with a review of the genus Thalassoalaimus de Man, 1893 from the Argentine coast - Martelli, Antonela; Russo, Virginia Lo; Villares, Gabriela; Ward, Catalina T. Pastor De (Zootaxa, 2017)
Two new free-living marine nematodes of the family Oxystominidae are described from San Antonio Bay (Río Negro) and San José Gulf (Chubut). Litinium australis sp. n., is characterized by having a rounded tail, by the first and second crown of cephalic setae with different lengths, gubernaculum with apophysis and by the presence of at least four precloacal papillae; Thalassoalaimus nestori sp. n., is characterized by having a conical tail, cephalic setae equal in length, gubernaculum with rounded and dorso-caudally directed apophysis and two precloacal papillae. An emended diagnosis of the genus Thalassoalaimus and a key to species are given.